Food Security, Agricultural Sector Resilience, and Economic Integration: Case Study of ASEAN+3 - Yudhatama, Putra; Nurjanah, Fitri; Diaraningtyas, Cassya; Revindo, Mohamad Dian (Jurnal Ekonomi & Studi Pembangunan, 2021)
The issue of food security has been increasingly critical in many parts of the world. In many countries people are facing food crisis and it has severe impact on their economies. Ensuring food security has become a global challenge with various dimensions. This study aims to examine the impact of intraregional trade on food security in the Association of Southeast Asian Nations (ASEAN) and three additional countries (China, Japan, South Korea), known as ASEAN+3. Using panel data regression analysis, the results show that intraregional trade and the level of trade openness have positive and significant effect to increase food security as it increases food production level in ASEAN+3 countries. In pursuing food security, ASEAN needs to enhance and accelerate its future cooperation agenda. The ASEAN member countries need to support the realization of ASEAN vision 2025, which will create a more dynamic and resilient ASEAN, capable of responding and adapting to various challenges through robust national and regional mechanisms to overcome various issues, including food security.